2003
DOI: 10.1056/nejmoa022157
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Atherosclerosis and Venous Thrombosis

Abstract: An association between atherosclerosis and venous thrombosisPrandoni, P.; Bilora, F.; Marchiori, A.; Bernardi, E.; Petrobelli, F.; Lensing, A.W.A.; Prins, M.; Girolami, A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
418
7
17

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(459 citation statements)
references
References 38 publications
17
418
7
17
Order By: Relevance
“…However, a number of studies have shown that idiopathic VTE is associated with an increased risk of subsequent cardiovascular events and that patients with idiopathic VTE have an increased prevalence of asymptomatic atherosclerotic lesions. [38][39][40] Because PCOS is associated with atherosclerotic disease, a relationship with venous diseases needs to be considered. Our findings, therefore, do have connotations that might be relevant in clinical settings.…”
Section: Commentmentioning
confidence: 99%
“…However, a number of studies have shown that idiopathic VTE is associated with an increased risk of subsequent cardiovascular events and that patients with idiopathic VTE have an increased prevalence of asymptomatic atherosclerotic lesions. [38][39][40] Because PCOS is associated with atherosclerotic disease, a relationship with venous diseases needs to be considered. Our findings, therefore, do have connotations that might be relevant in clinical settings.…”
Section: Commentmentioning
confidence: 99%
“…postpartum, history of cancer, recent leg fracture and immobilization). 17 More recently, lower levels of high density lipoprotein cholesterol and higher levels of low density lipoprotein cholesterol were found in men with VTE compared to controls. 18 A meta-analysis of cardiovascular risk factors and VTE found that hypertension and obesity conferred increased risk for VTE compared to controls (OR 1.51 and 2.33, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…The patients with pulmonary arterial thrombus had a higher probability of suffering coronary atherosclerosis and acute myocardial infarction. 6,7 Atherosclerosis is also a risk factor of pulmonary arterial thrombosis. 8 The patients with atherosclerosis had a higher probability of suffering PE.…”
Section: Discussionmentioning
confidence: 99%